Planning or free market economy in LDCs? - Emil Küng (Intereconomics, 1973)
On the face of it it looks as if there should be no great difference between less developed countries (LDCs) and the advanced national economies as far as planning is concerned. And yet in reality such differences do exist, even if they do not necessarily stem from the inequalities in the standard of living.
Keywords: 330; Development Policy